2019
DOI: 10.1093/eep/dvz007
|View full text |Cite
|
Sign up to set email alerts
|

Mature sperm small-RNA profile in the sparrow: implications for transgenerational effects of age on fitness

Abstract: Mammalian sperm RNA has recently received a lot of interest due to its involvement in epigenetic germline inheritance. Studies of epigenetic germline inheritance have shown that environmental exposures can induce effects in the offspring without altering the DNA sequence of germ cells. Most mechanistic studies were conducted in laboratory rodents and C.elegans while observational studies confirm the phenotypic phenomenon in wild populations of humans and other species including birds. Pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…While we expected that old parents would produce chicks with shorter telomeres, as found in other short-lived bird species in line with predictions of the Lansing effect ( Criscuolo et al, 2017 ; Bauch et al, 2019 ), our experimental approach found that old fathers produced daughters with longer telomeres, but only 3 months after hatching, potentially indicating an environmental or an age-dependent epigenetic effect ( Matsushima et al, 2019 ). Positive relationships between parental age and offspring telomere length have previously been foundin long- and short-lived bird species ( Asghar et al, 2015 ; Dupont et al, 2018 ; Brown A. M et al, 2021 ).…”
Section: Discussionsupporting
confidence: 76%
“…While we expected that old parents would produce chicks with shorter telomeres, as found in other short-lived bird species in line with predictions of the Lansing effect ( Criscuolo et al, 2017 ; Bauch et al, 2019 ), our experimental approach found that old fathers produced daughters with longer telomeres, but only 3 months after hatching, potentially indicating an environmental or an age-dependent epigenetic effect ( Matsushima et al, 2019 ). Positive relationships between parental age and offspring telomere length have previously been foundin long- and short-lived bird species ( Asghar et al, 2015 ; Dupont et al, 2018 ; Brown A. M et al, 2021 ).…”
Section: Discussionsupporting
confidence: 76%
“…Concurrently, very little is known about the molecular mechanisms involved, especially in poultry (Guerrero-Bosagna et al, 2018). These may include alterations in sperm miRNAs and lncRNAs (Wu et al, 2019), or putative RNA modifications, DNA methylation, and retained histones (Matsushima et al, 2019).…”
Section: Transgenerational Programmingmentioning
confidence: 99%
“…Recent studies confirm that sperm RNA content analysis is possible. 5,8 Poliovirus is an RNA virus and humans are it's only naturally occurring hosts 2. Prior to the 19th century no epidemics of acute flaccid paralysis due to poliomyelitis are recorded in any human culture 10 , the virus most likely infected nearly all humans universally 9,10 , had low rates of acute flaccid paralysis 10 and an even lower rate of mortality, infected individuals at a young age 9,10 and no poliomyelitis epidemics were recorded following European contact with previously separated populations including native American, native Australian, native Tasmanian and several others. Some authors report pre-contact poliomyelitis in Native American populations 11 .…”
Section: Introductionmentioning
confidence: 99%